2022
DOI: 10.1161/str.53.suppl_1.tmp82
|View full text |Cite
|
Sign up to set email alerts
|

Abstract TMP82: Comparison Of Direct Oral Anticoagulants To Vitamin K Antagonists For Treatment Of Cerebral Venous Sinus Thrombosis

Abstract: Introduction: Direct oral anticoagulants (DOACs) have gained popularity in treating cerebral venous thrombosis (CVT). However, studies comparing the use of DOACs to Vitamin K antagonists (VKA) among patients with CVT are limited. Methods: We conducted a single-center retrospective cohort study comparing VKA to DOAC-treated CVT patients. Clinical, radiographic findings and outcomes were compared. Continuous and categorical variables were compared using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…We excluded 235 of these articles; the most common reasons for exclusion were that studies did not compare our treatments of interest (n=122 studies), full texts were not available (n=31 studies), and studies enrolled fewer than 5 patients per group (n=26 studies). We therefore included 19 studies-3 RCTs 17,28,29 and 16 observational studies [12][13][14][15][16]23,[30][31][32][33][34][35][36][37][38][39] -in the systematic review (Figure 1).…”
Section: Summary Of Search and Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded 235 of these articles; the most common reasons for exclusion were that studies did not compare our treatments of interest (n=122 studies), full texts were not available (n=31 studies), and studies enrolled fewer than 5 patients per group (n=26 studies). We therefore included 19 studies-3 RCTs 17,28,29 and 16 observational studies [12][13][14][15][16]23,[30][31][32][33][34][35][36][37][38][39] -in the systematic review (Figure 1).…”
Section: Summary Of Search and Screeningmentioning
confidence: 99%
“…We identified 3 RCTs 17,28,29 and 16 observational studies. [12][13][14][15][16]23,[30][31][32][33][34][35][36][37][38][39] Fifteen studies reported on recurrent VTE, 16 studies reported on major hemorrhage, 16 studies reported on intracranial hemorrhage, 14 studies reported on death, and 12 studies reported on recanalization. In all studies, all outcomes reported were not significantly different between the 2 groups, except for 1 study 23 where the risks of major hemorrhage and intracranial hemorrhage were lower with DOAC treatment.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The overall occurrence of nonrecanalisation events was 19.6% of 1371 CVT patients. The analysis yielded similar events between the DOACs and warfarin groups (19.4% vs. 19.7%, I 2 = 0%, p = 0.65; RR = 0.95, 95% CI = 0.77–1.18) (Figure ) 7,10–12,14–16,18,19,21,23–25,28,29 . Additionally, analysing only studies of adult CVT also observed identical findings between DOACs and warfarin groups (RR = 0.97, 95% CI = 0.77–1.21, p = 0.78, I² =0%) 7,11,12,14–16,18,19,21,23–25,28,29 .…”
Section: Resultsmentioning
confidence: 59%
“…We included randomized and observational prospective and retrospective cohort studies of CVT patients in all age groups that compared the long‐term anticoagulation effects of DOACs and warfarin 6–30 . We excluded case reports, case series, review papers, and studies based on phenprocoumon anticoagulant 32,33 .…”
Section: Study Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation